2012
DOI: 10.1136/bmjopen-2012-000906
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia in Malawian neonates and young infants 2002–2007: a retrospective audit

Abstract: ObjectivesTo assess the causes of bacteraemia in young infants and susceptibility to first-line antibiotics (benzylpenicillin plus gentamicin) at the Queen Elizabeth Central Hospital (QECH), Malawi during 2002–2007.DesignRetrospective analysis of demographic and microbiological data using laboratory records.SettingQECH is Malawi's largest hospital with 7000 neonates admitted annually, 9% for septicaemia.PatientsAll infants aged 60 days or less admitted to QECH that had a blood culture taken over the 6-year per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…3 The neonatal mortality rate ofPakistan is 49/1000 live births. 4 In neonatal sepsis the commonest bacterial isolates are gram positive bacterial agents in developed countries 2 and according to a study conducted at a tertiary care hospital of Australia, staphylococcal sepsis is the most common bacterial isolate among gram positive bacteria. 5 Similarly, group B Streptococcus is considered as one of the most common pathogens in the early onset sepsis 6 but is relatively uncommon in countries like Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…3 The neonatal mortality rate ofPakistan is 49/1000 live births. 4 In neonatal sepsis the commonest bacterial isolates are gram positive bacterial agents in developed countries 2 and according to a study conducted at a tertiary care hospital of Australia, staphylococcal sepsis is the most common bacterial isolate among gram positive bacteria. 5 Similarly, group B Streptococcus is considered as one of the most common pathogens in the early onset sepsis 6 but is relatively uncommon in countries like Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…This is contrary to reports from other developing countries where CNS are usually amongst the least common organisms. 17 The reason for this might be because isolated CNS is excluded from analysis as it is often considered to be a contaminant. 17 Although CNS is often considered a contaminant, it is a pathogen in neonates, compromised hosts and patients with foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
“…17 The reason for this might be because isolated CNS is excluded from analysis as it is often considered to be a contaminant. 17 Although CNS is often considered a contaminant, it is a pathogen in neonates, compromised hosts and patients with foreign bodies. 8 Further evaluations such as a repeat blood culture are required to determine the clinical significance of CNS.…”
Section: Discussionmentioning
confidence: 99%
“…A similar review of neonatal blood cultures done over that same period of time showed that 53% of the pathogens were Gram-positive and 47% Gram-negative. The four most common pathogens were S. aureus , GBS, Salmonella Typhimurium, and E. coli 22. Klebsiella sp , Acinebacter sp and Enterobacter sp , all considered nosocomial infections, accounted for 7.3%, 3.1% and 4.6% of the Gram negative pathogens The results of our study differ because we included all cases of possible severe bacterial infection, as this reflects clinical practice; only 147 (45%) blood or CSF samples grew bacteria of which 62 (42%) were coagulase negative staphylococci that may, or may not, have been contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…Cephalosporins are bactericidal antibiotics and although CNS penetration is modest, higher doses safely achieve therapeutic CSF drug levels. In Malawi benzylpenicillin is appropriate for GBS infections and for most S. pneumoniae infections 21,2223,24…”
Section: Introductionmentioning
confidence: 99%